Exploration of Cellulose-Based Matrix Materials: A Comparative Study in the Development of Radar Absorbing Materials for Military Applications - Indriani, Sulfi; Sri Yanto; I Nengah Putra (Jurnal Serambi Engineering, 2026)
Exploring cellulose-based matrix materials for Radar Absorbing Materials (RAM) is a strategic way to advance defence technology, emphasising both technical effectiveness and environmental sustainability. This study uses a systematic literature review (SLR) approach to identify, evaluate and analyse previous research on the use of cellulose-based matrices compared with conventional materials such as epoxy, polyurethane (PU) and graphene. Comprehensive data was collected from indexed scientific databases (ScienceDirect, SpringerLink, Wiley and Google Scholar), covering publications from 2013 to 2025. The findings reveal that, when combined with graphene or carbon nanotube (CNT) fillers, cellulose aerogels can achieve reflection loss (RL) values as low as −70 dB, outperforming most conventional materials. Furthermore, carboxymethyl cellulose (CMC) with an ultrathin thickness of only 0.028 mm demonstrates high absorption efficiency of 98.2%. While limitations remain in terms of bandwidth and thermal stability, cellulose offers significant advantages, including low density, low cost, biodegradability and the availability of renewable resources. These results highlight cellulose as a highly promising alternative matrix material for RAM in military applications, while simultaneously supporting the green defence agenda and strengthening the resilience of the defence industry.